Extrication time prediction tool. Issue 5 (17th April 2014) - Nutbeam, Tim; Fenwick, Rob; Hobson, Charles; Holland, Vikki; Palmer, Michael
Abstract : Background: Many patients will require extrication following a motor vehicle collision (MVC). Little information exists on the time taken for extrication or the factors which affect this time. Objective: To derive a tool to predict the time taken to extricate patients from MVCs. Methods: A prospective, observational derivation study was carried out in the West Midland Fire Service's metropolitan area. An expert group identified factors that may predict extrication time—the presence and absence of these factors was prospectively recorded at eligible extrications for the study period. A step-down multiple regression method was used to identify important contributing factors. Results: Factors that increased extrication times by a statistically significant extent were: a physical obstruction (10 min), patients medically trapped (10 min per patient) and any patient physically trapped (7 min). Factors that shortened extrication time were rapid access (−7 min) and the car being on its roof (−12 min). All these times were calculated from an arbitrary time (which assumes zero patients) of 8 min. Conclusions: This paper describes the development of a tool to predict extrication time for a trapped patient. A number of factors were identified which significantly contributed to the overall extrication time.